Of donkeys, elephants, and dehumanization: exploring the content and implications of stereotypes of Republicans, Democrats, Libertarians, and independents - Brown, Elizabeth R.; Phills, Curtis E.; Veilleux-Mesa, Candice J. (Frontiers in Social Psychology, 2025)
Within the United States (U.S.), the political landscape is polarized between two major parties: the Democratic Party and the Republican Party. Elite polarization has led to legislative gridlock and labeling the ‘other' major party as different, which hinders social change because less receptivity to the other party's ideas and less willingness to accept criticism from members of the other party. Non-major political groups and political independents are essential but understudied routes to social change because they may not be perceived as electoral and viewpoint competition to major political groups. Previous literature has examined the stereotypes of major as opposed to non-major political groups and political independents. The present research examines how fundamental stereotypes (warmth and competence) are associated with Republicans, Democrats, Libertarians, and political independents and the implications of those stereotypes for a critical intergroup outcome (i.e., dehumanization). In a sample of undergraduates (agemedian = 20) and a sample of older adults (agemedian = 34), fundamental stereotypes about major political groups but not Libertarians or independents reflect perceived competition. The pattern of fundamental stereotypes applied to Libertarians and independents is consistent with stereotypes of admired groups and our hypothesis that non-major political groups and political independents can be a vector for social change. Further, fundamental competence stereotypes about one's own major political group were associated with the dehumanization of the other major political group. In contrast, fundamental stereotypes of major political groups were not associated with the dehumanization of Libertarians or independents. Given that non-major political groups and political independents are not viewed as competition to major political groups, future research should examine how non-major political groups and political independents could reduce political polarization in the U.S.